2007
DOI: 10.1007/s10811-007-9190-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of optimal depth and photon irradiance for cultivation of the brown alga, Sargassum fulvellum (Turner) C. Agardh

Abstract: This study was aimed at determining the optimal depth and photon irradiance for growth of Sargassum fulvellum. Sampling and measurement of underwater irradiance were carried out at farms cultivating S. fulvellum at Wando, southwestern coast of Korea, from May 2004 to April 2005. Growth of thalli, underwater irradiance and photosynthetic quantum yield were measured over a range of depths for three culture stages. During their nursery cultivation stage (Stage I), length increase was greatest at 1.5 m depth (2.5±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
11
0
4
Order By: Relevance
“…1), whilst nursery and on-growing culture techniques are similar to those of Sargassum fulvellum (Turner) C. Agardh as described by Hwang et al (2007). They reported that growth of S. fulvellum could be optimized by controlling the depth at which the cultivation ropes were held.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1), whilst nursery and on-growing culture techniques are similar to those of Sargassum fulvellum (Turner) C. Agardh as described by Hwang et al (2007). They reported that growth of S. fulvellum could be optimized by controlling the depth at which the cultivation ropes were held.…”
Section: Discussionmentioning
confidence: 90%
“…The probe was held at each depth for 5 min, during which time an average reading was taken. Surface PAR measurements were taken between each depth reading at the start and end of deth profiles at each site as described by Hwang et al (2007).…”
Section: Cultivation Site and Periodmentioning
confidence: 99%
“…Most previous studies over multiple generations of algae have been conducted at laboratory scale under controlled conditions (Monro and Poore 2004;Xu et al 2012). In contrast, studies conducted at a larger scale have been focused on environmental parameters with the exclusion of multiple generations (Hwang et al 2007;Edwards and Dring 2011;Handå et al 2013). As an example, we have shown considerable variation in productivity of Ulva sp.…”
Section: Released Swarmers (×10mentioning
confidence: 89%
“…Notably, most environmental conditions, including nutrients, water temperature and salinity, remained relatively constant for the experimental duration of 5 months, while the average photosynthetically active radiation nearly halved. Light is important for algal growth and productivity (Taylor et al 2001;Pang and Lüning 2004a;Hwang et al 2007;Edwards and Dring 2011) and affects reproductive output, maturation and quality of released swarmers (Makarov and Voskoboinikov 2001;Dan et al 2002;Pang and Lüning 2004b;Lüning et al 2008). However, our findings clearly demonstrate generational effects in combination with environmental effects, such that both require consideration for the intensive production of biomass.…”
Section: Discussionmentioning
confidence: 99%
“…집약적인 양식을 통한 해조류의 대량 양식기 술은 중국, 일본 그리고 우리나라의 김, 미역 및 다시마 (Kawashima, 1984;Tseng, 1987;Ohno and Matsuoka, 1993;Oohusa, 1993) 등에서 발달되어왔다. 감태 (Ecklonia cava Kjellman)는 해중림을 구성하는 대형 갈조류로서 연안 생태계에서 1차 생산자로서의 중요한 기능 을 담당하고 있으며 (Kang and Yoo, 1993;Brown and Lamare, 1994), 해중림 조성용, 식용 또는 기능성 물질의 추출원 (Athukorala et al, 2006;Hong et al, 2006) 감태의 안정적인 대량양식 생산을 유도하기 위해서는 최근 모자반 (Hwang et al, 2007)과 곰피 (Hwang et al, 2009 (Fig. 1A).…”
Section: 서 론 해조류는 아시아 지역 국가들에서 인간의 식량원이나 해산unclassified